Heterogeneous firms, trade, and economic policy: Insights from a simple two-sector model - Michael Pflüger; Stephan Russek (Institute for the Study of Labor (IZA), 2011)
The robust empirical finding that exporting firms are systematically different from firms that merely serve domestic consumers has inspired the development of a new brand of trade theory, the theory of heterogeneous firms and trade. The establishment of a canonical model due to Melitz (2003) has induced a recent wave of research which explores various policy issues and policy instruments. This paper uses a simple tractable two-sector model of monopolistic competition as unifying framework to bring out key lessons of this recent research. We address the gains from trade, country asymmetries involving technology potentials, market sizes, trade openness and various business conditions as well as the international repercussions that emerge when countries non-cooperatively choose entry subsidies and their levels of basic research. We also reinvestigate the process of market exit.
urn:nbn:de:101:1-201111213525
Keywords: F12; F13; F15; L25; 330; firm heterogeneity; monopolistic competition; economic policies and welfare; Unternehmen; Mehr-Sektoren-Modell; Monopolistischer Wettbewerb; Außenwirtschaft; Wirtschaftspolitik; Wohlfahrtsanalyse; Theorie